Magenta and me - Reber, Deborah; Bishop, Don (New York : Simon Spotlight, 2000)
From helping each other at school to sharing a special play date, Blue and Magenta do lots of fun things together as best friends. Features rebuses.
"#2."
Based on the TV series Blues clues created by Traci Paige Johnson, Todd Kessler, and Angela C. Santomero.
7 11 13 29
Keywords: Best friends -- Fiction; Dogs -- Fiction; Stories in rhyme; Rebuses; Rebuses; Blue -- Fiction